Chronic stress synergizes with Listeria monocytogenes to promote intestinal adenomagenesis via myeloid-derived suppressor cells - Qi, Pingqian; Yin, Lili; Wei, Ruijia; Yang, Siyuan; Liu, Ziqing; Huang, Ping; Yu, Qiwen; Xiong, Suyi; Wang, Mengmeng; Deng, Yanjuan; Hu, Jinping; Zhou, Lv; et al. (Frontiers in Immunology, 2025)
BackgroundChronic stress and gut dysbiosis are established risk factors for colorectal adenocarcinoma, yet their synergistic effects on the development of intestinal precancerous lesions remain poorly understood.MethodsThis study investigates the molecular mechanisms through which chronic stress interacts with opportunistic pathogen Listeria monocytogenes to drive intestinal tumorigenesis in ApcMin/+ mice, with particular focus on the involvement of tumor immune microenvironment remodeling.ResultsThe combination of L. monocytogenes infection and chronic stress, rather than bacterial infection alone, significantly increased colonic adenoma burden and epithelial dysplasia, suggesting that chronic stress establishes a permissive microenvironment for opportunistic pathogens to exert pro-tumorigenic effects. Mechanistically, chronic stress downregulated intestinal epithelial Muc-2 expression and reduced microbial diversity, thereby compromising mucus/microbial barrier integrity and enhancing L. monocytogenes colonization. Under dual stress-pathogen exposure, we observed the expansion of myeloid-derived suppressor cells (MDSCs) in spleen and the upregulation of IL-6 in colonic mucosa, which facilitated MDSCs recruitment to tumor sites. Infiltrating MDSCs driven CD8+ T cell depletion through cAMP/PKA/CREB signaling, leading to the establishment of immunosuppressive microenvironment.ConclusionOur results propose that chronic stress-induced gut barrier disruption may serve as a prerequisite for opportunistic pathogens to accelerate the development of precancerous lesions. Their synergistic effects reshape systemic/local immune responses, creating a microenvironment conducive to malignant transformation and tumor cell survival. These preliminary findings highlight potential clinical applications of psychological interventions and immune modulation strategies in preventing intestinal carcinogenesis.